2017
DOI: 10.1124/jpet.117.242909
|View full text |Cite
|
Sign up to set email alerts
|

Acalabrutinib (ACP-196): A Covalent Bruton Tyrosine Kinase Inhibitor with a Differentiated Selectivity and In Vivo Potency Profile

Abstract: Several small-molecule Bruton tyrosine kinase (BTK) inhibitors are in development for B cell malignancies and autoimmune disorders, each characterized by distinct potency and selectivity patterns. Herein we describe the pharmacologic characterization of BTK inhibitor acalabrutinib [compound 1, ACP-196 (4-[8-amino-3-[(2)-1-but-2-ynoylpyrrolidin-2-yl]imidazo[1,5-]pyrazin-1-yl]--(2-pyridyl)benzamide)]. Acalabrutinib possesses a reactive butynamide group that binds covalently to Cys481 in BTK. Relative to the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
343
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(369 citation statements)
references
References 44 publications
(46 reference statements)
6
343
0
5
Order By: Relevance
“…2,17,18 Acalabrutinib, a second generation, irreversible BTK inhibitor, was developed as a selective BTK inhibitor to avoid the off-target side effects seen ibrutinib. [7][8][9] Zanubrutinib, a next-generation, irreversible BTK inhibitor, was developed as a selective BTK inhibitor and has received approval for treatment of relapsed refractory mantle cell lymphoma. 19 Studies are ongoing in evaluating the drug's safety and efficacy in CLL.…”
Section: Role Of Bruton's Tyrosine Kinase Inhibitors In Cllmentioning
confidence: 99%
See 1 more Smart Citation
“…2,17,18 Acalabrutinib, a second generation, irreversible BTK inhibitor, was developed as a selective BTK inhibitor to avoid the off-target side effects seen ibrutinib. [7][8][9] Zanubrutinib, a next-generation, irreversible BTK inhibitor, was developed as a selective BTK inhibitor and has received approval for treatment of relapsed refractory mantle cell lymphoma. 19 Studies are ongoing in evaluating the drug's safety and efficacy in CLL.…”
Section: Role Of Bruton's Tyrosine Kinase Inhibitors In Cllmentioning
confidence: 99%
“…5,6 Acalabrutinib, a second generation and more selective Bruton's tyrosine kinase (BTK) inhibitor, was developed to maximize efficacy while minimizing ibrutinib-associated adverse events hypothesized to be secondary to ibrutinib's off-target effects. [7][8][9] This review will summarize the development, pre-clinical evaluation, and key clinical trials that have demonstrated acalabrutinib's efficacy and toxicity profile in CLL.…”
Section: Introductionmentioning
confidence: 99%
“…Bruton tyrosine kinase (BTK) inhibitors have greatly improved the spectrum of treatment options in mantle cell lymphoma (MCL) [1][2][3][4]. Acalabrutinib is a highly selective, orally administered, and potent BTK inhibitor with limited off-target activity [5]. Acalabrutinib was approved in 2017 by the US Food and Drug Administration for the treatment of relapsed/refractory MCL based on clinical data from the open-label, multicenter, phase 2 ACE-LY-004 study of acalabrutinib 100 mg twice daily [1].…”
Section: To the Editormentioning
confidence: 99%
“…Despite their activity as single agents or in combination, ibrutinib and idelalisib present toxicities (de Weerdt et al , ) that can limit their use in clinical practice and novel compounds are in development to increase the therapeutic window for these classes of agents. Acalabrutinib (ACP‐196) is an irreversible BTK inhibitor with higher selectivity for its target than ibrutinib (Barf et al , ; Herman et al , ). Preclinical anti‐tumour activity in human and mouse models of chronic lymphocytic leukaemia (CLL) (Golay et al , ; Herman et al , ; Patel et al , ) and in a canine diffuse large B‐cell lymphoma (DLBCL) model (Harrington et al , ) have been followed by clinical efficacy data in patients with relapsed CLL or relapsed/refractory mantle cell lymphoma (MCL) with approval by the U.S. FDA (Byrd et al , ; Markham & Dhillon, ; Wang et al , ).…”
Section: Introductionmentioning
confidence: 99%